EXPLORING THE ANTIPSYCHOTIC EFFECTS OF PIPER LONGUM ETHANOLIC FRUIT EXTRACT IN A RODENT MODEL - Himanshu Joshi; Kokkula Pavan Kumar; K. Ashok Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
This research explores the potential antipsychotic effects of the ethanolic extract derived from the fruits of Piper longum (EEPL) in Wistar albino rats, with a focus on its possible therapeutic application in neuropsychiatric conditions. To assess its efficacy, a series of well-established neurobehavioral tests were utilized, including Cook’s pole climbing apparatus, the Actophotometer, and the Open Field Test. These models are instrumental in evaluating conditioned behavior, spontaneous locomotion, and anxiety-related responses in rodents. EEPL was administered orally at two dosage levels 200 mg/kg and 400 mg/kg—to analyze its dose-dependent pharmacological effects. The treated animals demonstrated significant shifts in locomotor behavior and pole climbing latency, which are recognized parameters in the assessment of antipsychotic activity. Notably, a reduction in latency time during pole climbing trials suggested improved behavioral responses, possibly due to alterations in central neurotransmitter regulation. To delve deeper into the mode of action, both biochemical assays and tissue-level investigations were conducted. Immunohistochemical evaluation revealed a marked downregulation of tumor necrosis factor-alpha (TNF-α), an inflammatory cytokine often implicated in neurodegenerative and psychiatric disorders. The suppression of this marker indicates potential anti-inflammatory and neuroprotective properties of EEPL. Histological analysis of the brain and liver tissues further supported these findings. Neuronal architecture in EEPL-treated rats appeared intact, with negligible signs of degeneration, suggesting a neuroprotective effect. Additionally, hepatic tissue showed no pathological changes, reinforcing the extract’s safety and non-toxic nature at the administered doses. Collectively, the study provides compelling evidence that Piper longum fruit extract may possess bioactive components with significant antipsychotic and neuroprotective activities. The combination of behavioral enhancements, decreased inflammatory signaling, and maintained cellular structure points to its promise as a natural therapeutic candidate for treating neuropsychiatric and degenerative disorders. Further studies are warranted to isolate and characterize the active constituents, elucidate their interaction with neurochemical pathways, and expand the investigation through advanced preclinical and clinical trials.